Patterns and Determinants of Blood and Blood Products Transfusion in Neonate: An Experience of Single Institute - Hameed , Numan Nafie; Ameen, Hiba Khalil; Faraj, Safa (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Neonates requiring intensive care are among the most frequently transfused group of patients. Indications for blood transfusion in neonates could be physiological or pathological. However, despite frequent blood transfusions in neonates in Iraq, there is a paucity of studies on its indications and patterns among neonates in our setting. AIM: The aim of the study is to shed light on the details of giving blood and blood products in the unit of neonate in Children Welfare Teaching hospital, Baghdad and the justifications for giving and its complication. PATIENTS AND METHODS: A descriptive study (cross-section study) includes all neonates admitted to neonatal care unit in Children Welfare Teaching Hospital. The study includes a group of newborns who were blood transfused during their admission to hospital, over a period of 6 months from October 1, 2019 to March 30, 2020. All data were collected from each patient and recorded in predesigned forma, these data include patient’s clinical data and analyzed using descriptive statistics. RESULTS: A total number of cases admitted over a period of 6 months were 862. One hundred and forty neonates received blood and its products transfusion, (61.4%) were male and (38.6%) were female, (62.9%) received packed red blood cells (PRBCs) followed by (18.6%) received exchange transfusion, (11.4%) received Fresh frozen plasma and (7.1%) received platelets. Most neonates received blood products transfused at (3–4) weeks. Post-natal age and were term babies (37–41) weeks. Gestational age mostly received PRBCs. CONCLUSIONS: Most neonates with a high rate of blood and blood product transfusion were males, term, need assistant ventilation, and transfused at 3–4 weeks postnatal age.